IMPLEMENTASI PENDEKATAN TPACK DALAM PENGAJARAN KETERAMPILAN MEMBACA PEMAHAMAN PADA SISWA KELAS VIII SMP MUHAMMADIYAH KOTA MAKASSAR - Hanana Muliana; Muhammad Dahlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of implementing the Technological Pedagogical and Content Knowledge (TPACK) approach in teaching reading comprehension skills to junior high school students. The research employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The participants consisted of two classes, an experimental class taught using the TPACK approach and a control class taught through conventional methods, each comprising 30 students. The research instrument was a reading comprehension test administered before (pretest) and after (posttest) the treatment. Data were analyzed using descriptive and inferential statistics through a t-test at a 0.05 significance level. The findings indicated a significant improvement in the reading comprehension skills of the experimental group, with an average posttest score of 83.47 compared to 74.20 for the control group. The obtained t-value of 5.281 exceeded the t-table value of 2.000, confirming that the TPACK approach positively influences students’ reading comprehension ability. In addition to cognitive enhancement, TPACK-based learning also fostered higher motivation and active participation among students during the learning process. Therefore, the TPACK approach can serve as an innovative alternative in Indonesian language instruction to improve students’ reading comprehension skills at the junior high school level.